A percepção dos associados em relação às ações de sustentabilidade : um estudo de caso de uma cooperativa de crédito - Lutz, Nataly (2022)
New parameters that considerably change the way companies position themselves in front of their public and society in general appear in the corporate world. Sustainability in cooperatives focuses on increasing the positive economic, social and environmental impact, reducing adverse impacts and creating value for members, employees, the community and other stakeholders. Given that, even with the difficulty and disparity of the concept, it can be deduced that in addition to aspects related to economic growth, social and environmental issues must also be considered for the development of a region. Through the present work, the perception they have about the concept of sustainability of the Cooperative was analyzed. For that, a qualitative study was carried out with a group selected by judgment of the members of the Cooperative. It was understood that the associates experience sustainability within the Cooperative, taking into account the strategic drivers. However, associates are unable to identify sustainability aspects related to the Sicredi brand, mainly due to inaccessibility.